2010
DOI: 10.1007/s10238-010-0099-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator inhibitor-1 polymorphisms (−844 G>A and HindIII C>G) in systemic lupus erythematosus: association with clinical variables

Abstract: Systemic lupus erythematosus (SLE) is a systemic autoimmune disease characterized by the presence of autoantibodies against nuclear autoantigens as well as cytoplasmic and circulating proteins. Recent studies have demonstrated mechanisms responsible for modulation of the immune response by the plasminogen activator inhibitor-1 (PAI-1). Furthermore, the endogenous PAI-1 has shown to promote a Th2 immune response. We assessed the -844 G>A and HindIII C>G PAI-1 polymorphisms in SLE. In a case-control study of 71 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…Regarding the distribution of genotype and allele frequencies of both polymorphisms, for the HindIII C/G polymorphism we found a high frequency of C allele, similar to previous reports in Mexican mestizo population and Caucasian population, however the G allele frequency was lower in Mexican population [18,21,29]. On the other hand, the -844 G/A polymorphism we observed that is distributed inversely to those reported in Caucasian populations, in which the A allele is more frequent than the G allele [12,18,19].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding the distribution of genotype and allele frequencies of both polymorphisms, for the HindIII C/G polymorphism we found a high frequency of C allele, similar to previous reports in Mexican mestizo population and Caucasian population, however the G allele frequency was lower in Mexican population [18,21,29]. On the other hand, the -844 G/A polymorphism we observed that is distributed inversely to those reported in Caucasian populations, in which the A allele is more frequent than the G allele [12,18,19].…”
Section: Discussionsupporting
confidence: 90%
“…Association studies have shown that polymorphisms located in the promoter region of PAI-1 gene shows a relationship with the concentrations of lipids (low HDL) in Mexico-American population [16,17]. One of the polymorphisms in the promoter PAI-1 gene is the -844 G/A polymorphism, which has been associated with risk factors such as increased plasma levels of PAI-1, glucose, insulin resistance, triglycerides and low HDL, as well as with several diseases including deep vein thrombosis, coronary artery disease, rheumatoid arthritis and systemic lupus erithematosus [18-21]. Other SNP that is interesting is the HindIII C/G polymorphism located in the 3' untranslated region (UTR) of PAI-1 gene, which has been related to high levels of cholesterol and insulin in myocardial infarction patients [22].…”
Section: Introductionmentioning
confidence: 99%
“…As it was established previously, we found differences in the genetic distribution in the HS group compared with other populations, including Europeans, Asians, and Sub-Sahara Africans, but not with the African American group and a previous report of Western Mexicans [ 16 ]. The own genetic structure of the Mexican Mestizo population, composed mainly with Spanish (53.2%) and American native (30.8%) genes, can explain these differences [ 23 ].…”
Section: Discussionsupporting
confidence: 69%
“…We compared the HS frequencies with other populations. The A allele prevalence was 23% in Sub-Saharan African, 27% in Mexican, 28% in Afro-American, 41% in Hispanic, 49% in Asian, and 56% in European populations [ 16 , 18 ]. The genetic distribution of the -844 G>A polymorphism in this cohort was different to those reported in Sub-Saharan African, Asian, and Europeans populations ( P < 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation